Links between Irrigation, Agriculture, Level of Living and Poverty Scenario in West Bengal - Ghosh, Souvik; Panda, D. K.; Nayak, A. K.; Nanda, P.; Verma, H. C. (Indian Journal of Extension Education, 2015)
An analysis of irrigation, agriculture, level of living and poverty linkages in eighteen districts of West Bengal was carried  out. District-wise scenario of irrigation, agriculture, livelihood and poverty revealed with the help of different indices  developed for the study. The values of Groundwater Development Index and Composite Irrigation Index were found low  to very low for eight districts. Six districts showed high agricultural development while seven and five districts showed  medium and low Agricultural Development Index values, respectively. Level of living of eleven and six districts was  found medium and low, respectively. Poverty Ratio Index values of nine districts showed very high to high poverty level.  The links and/or missing links between irrigation resources, agriculture development, poverty and level of living were  explored.
Keywords: Agricultural development; irrigation; groundwater development; level of living; rural poverty